Impact resistance of hygrothermally conditioned composite laminates with different lay-ups. (March 2015) - Zhong, Yucheng; Joshi, Sunil Chandrakant
Low-velocity impact testing was conducted on carbon/epoxy composite laminates exposed to hygrothermal environments. Besides normal laminates, staggered lay-up structures were made from unidirectional prepreg materials. The specimens were immersed in water at 80℃ for different durations before impact testing. Experimental data showed that moisture played a positive role by improving the impact resistance of composite laminates. Laminates with higher moisture level could behave elastically up to higher strain levels and retain their resistance to the striking impactor to larger deflections. After absorbing moisture, more of the impact energy was dissipated by the specimen through elastic deformation and less damage was induced to the laminate. Little degradation in the fiber/matrix interface was observed from SEM graphs. It is postulated that absorbed moisture improved the ductility of the epoxy resin by promoting chain segmental mobility of the polymer molecules, which eventually lead to the better impact response of laminates with higher moisture content.